2020
DOI: 10.3892/ijmm.2020.4725
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 inhibits HeLa cell energy metabolism and induces apoptosis by upregulating voltage‑dependent anion channel 1

Abstract: 20(S)-Ginsenoside Rh2 [20(S)-GRh2], one of the main active components of Panax ginseng, induces apoptosis in a wide range of cancer cell types. The present study found that 20(S)-GRh2 reduces mitochondrial membrane potential, decreases adenosine triphosphate generation and induces reactive oxygen species in HeLa cervical cancer cells. In addition, 20(S)-GRh2 activated mitochondrion-dependent apoptosis and inhibited both mitochondrial oxidative phosphorylation and glycolysis in HeLa cells. It was found that vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…HK1 and HK2 are known to be mitochondrial hexokinase isotypes because they participate in glucose metabolism by binding to mitochondria. They are mainly expressed in mitochondria, but there is also a small expression in the cytoplasm [ 5 , 6 , 7 ]. To study the expression of HK, we first studied the mRNA and overall protein levels of HK1 and HK2 using quantitative real-time PCR (Q-PCR) and Western blotting, respectively, in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HK1 and HK2 are known to be mitochondrial hexokinase isotypes because they participate in glucose metabolism by binding to mitochondria. They are mainly expressed in mitochondria, but there is also a small expression in the cytoplasm [ 5 , 6 , 7 ]. To study the expression of HK, we first studied the mRNA and overall protein levels of HK1 and HK2 using quantitative real-time PCR (Q-PCR) and Western blotting, respectively, in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…A decreased expression of HK and dissociation from mitochondria reduces glucose metabolism, promotes mitochondrial dysfunction, and leads to a disruption of the NAD+/NADH ratio, the depolarization of membrane potential and the opening of mitochondrial permeability transition pores. It further promotes mitochondrial reactive oxygen species (ROS) release and NLRP3 inflammasome activation [ 7 , 8 , 9 , 10 , 11 , 12 ]. Consistently with these observations, we found decreased expression of HK and combination of it with mitochondria in N2a-sw cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of mitochondrial dysfunction was considered as a possible mechanism of G-Rh2-induced cytotoxicity (36). A previous study by our group suggested that G-Rh2 upregulated voltage-dependent anion channel 1 to trigger the mitochondrial translocation of BAX, promoting cytochrome c release and initiating mitochondrial-dependent apoptosis in HeLa cells (24). In the present study, it was revealed that the effect of G-Rh2 on the dissipation of the MMP and the reduction in ATP generation in HeLa cells was much stronger than that in C33A cells, consistent with the cell viability and apoptosis results.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rh2 activated mitochondriadependent apoptosis pathway and inhibited mitochondrial oxidative phosphorylation and glycolysis in HeLa cells. In addition, ginsenoside Rh2 inhibited energy metabolism and induced apoptosis in HeLa cells by upregulating voltage-dependent anion channel 1 (VDAC1), which caused MMP depolarization and ROS production [145]. It is suggested that VDAC1 is a new target of ginsenoside Rh2.…”
Section: Diterpenoids and Terperpenoidsmentioning
confidence: 99%